Effect of inpatient and outpatient care on treatment outcome in tuberculosis: a cohort study - Marli S. Rocha; Gisele P. Oliveira; Valéria Saraceni; Fernanda P. Aguiar; Claudia M. Coeli; Rejane S. Pinheiro (Pan American Health Organization, 2018)
Objective. To identify individual- and health services-related factors associated with deaths in subjects diagnosed with tuberculosis (TB). Methods. A nonconcurrent cohort study with passive follow-up was conducted using a probabilistic linkage method to analyze a sample of patients diagnosed and reported as having TB in 2006 and followed up until 2008. New cases, cases with previous treatment (readmission after loss to follow-up or relapse), and transfers across health services were included. Proportional hazards models were used to estimate the independent effect of covariates related to the individual and to the health services on mortality from all causes. Results. Age above 60 years, admission to a hospital with emergency services, HIV-associated TB, and readmission to an outpatient facility after disease relapse or loss to follow-up were identified as risk factors for death. Variables related to process and results indicators of Brazil's National TB Program were not associated with mortality from all causes. Conclusions. Advanced age, previous treatment for TB, and treatment at a secondary-level outpatient facility or a hospital with emergency services on site were associated with mortality in TB patients. Better strategies to improve TB care delivered at health units are needed to prevent death from TB, especially among the elderly.